Enhancing Energy Flexibility: A Case Study on Peer-to-Peer (P2P) Energy Trading Between Electric Vehicles and Microgrid - Biswas, Chanchal; Sharma, Anik; Prianka, Yingking Mitra (Control Systems and Optimization Letters, 2025)
In order to better understand how Peer-to-Peer (P2P) energy trading between EVs and microgrids might improve energy flexibility, lower costs, and facilitate the integration of renewable energy sources, this case study examines the viability and advantages of this innovative strategy. By allowing EVs to trade energy directly with other EVs or microgrid components, P2P energy trading establishes a decentralized energy market that maximizes the distribution and use of energy. Using real-world situations, this study assesses the technical and economic elements of peer-to-peer (P2P) trading and its effects on user involvement, energy management, and grid stability. By enabling EVs to trade energy directly with one another or with microgrid components, P2P energy trading creates a decentralized energy market that optimizes energy distribution and consumption. The findings demonstrate that P2P trading can greatly lower energy expenses, ease system congestion, and increase energy consumption efficiency overall. P2P trade is a viable option for future energy systems since it guarantees safe and transparent transactions through the use of blockchain technology and smart contracts. Microgrids can adapt to changes in the supply of renewable energy by using P2P technologies. EV batteries, for instance, can store extra solar energy during periods of high production and release it to the grid or other EVs when demand spikes. The results demonstrate how P2P energy trading can help ease the shift to a user-centric, decentralized, and sustainable energy economy.